Conductor substrate, and wiring substrate and method for manufacturing wiring substrate
A conductor substrate with a stretchable resin layer and conductor foil/plating film addresses efficiency and resistance issues in existing stretchable wiring boards, achieving high productivity and heat resistance.
Patent Information
- Application Number
- JP2024173328
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-04-21
- Filing Date
- 2024-10-02
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing methods for imparting stretchability to wiring boards, such as pre-stretching metal thin films and using conductive pastes, suffer from low production efficiency and high resistance issues, respectively.
A conductor substrate is developed with a stretchable resin layer and a conductor foil or plating film, utilizing a combination of a stretchable resin layer and a conductor foil or plating film to enhance manufacturing efficiency and reduce resistance.
The proposed conductor substrate allows for high productivity and high heat resistance, with the stretchable resin layer maintaining its properties even under strain.
Smart Images

Figure 2025000932000001_ABST
Abstract
Description
[Technical field]
[0001] One aspect of the present invention relates to a wiring board capable of having high stretchability and a manufacturing method thereof, while another aspect of the present invention relates to a conductive substrate that can be used to form such a wiring board. [Background technology]
[0002] In recent years, in the fields of wearable devices and healthcare-related devices, for example, there is a demand for devices that can be used along curved surfaces or joints of the body and that have flexibility and stretchability so that connection failures are unlikely to occur when the devices are put on or taken off. To configure such devices, wiring boards or substrates with high stretchability are required.
[0003] Patent Document 1 describes a method for encapsulating semiconductor elements such as memory chips using an elastic resin composition. Patent Document 1 mainly examines the application of the elastic resin composition to encapsulation. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2016 / 080346 Summary of the Invention [Problem to be solved by the invention]
[0005] As a method for imparting stretchability to wiring boards, a pre-stretch method has been proposed in which a metal thin film is evaporated onto a pre-stretched substrate, and then the substrate is relaxed to form wrinkled metal wiring. However, this method requires a long vacuum process to form conductors by metal evaporation, and is therefore insufficient in terms of production efficiency.
[0006] A method has also been proposed for easily forming stretchable wiring by printing a stretchable conductive paste in which conductive particles are dispersed in a stretchable elastomer. However, wiring made from conductive paste has a problem in that it has a higher resistance than metal wiring, and the resistance increases when stretched.
[0007] In light of these circumstances, an object of one aspect of the present invention is to provide a conductive substrate that enables a wiring board having elasticity to be produced easily with high productivity. [Means for solving the problem]
[0008] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by combining an elastic resin layer and a conductor foil. That is, one aspect of the present invention provides a conductor substrate having an elastic resin layer and a conductor foil provided on the elastic resin layer.
[0009] Furthermore, the present inventors have found that the above-mentioned problems can be solved by forming a conductive plating film as a conductor layer on an elastic resin layer. That is, another aspect of the present invention provides a conductive substrate having an elastic resin layer and a conductive plating film provided on the elastic resin layer. Effect of the Invention
[0010] The stretchable wiring board according to one aspect of the present invention can be easily manufactured from a conductor substrate with high productivity. The conductor substrate according to some aspects of the present invention can have high heat resistance. [Brief description of the drawings]
[0011] [Figure 1] 1 is a stress-strain curve showing an example of measuring the recovery rate. [Diagram 2] FIG. 1 is a plan view illustrating an embodiment of a wiring board. [Diagram 3] 1 is a graph showing a temperature profile in a heat resistance test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, several embodiments of the present invention will be described in detail, however, the present invention is not limited to the following embodiments.
[0013] The conductor substrate according to one embodiment has an elastic resin layer and a conductor layer provided on one or both sides of the elastic resin layer. In this specification, the conductor substrate may be referred to as a "laminated plate with a conductor layer". The wiring substrate according to one embodiment has an elastic resin layer and a conductor layer provided on one or both sides of the elastic resin layer and forming a wiring pattern. The conductor layer may be a conductor foil or a conductor plating film.
[0014] The elastic modulus of the conductor foil may be 40 to 300 GPa. When the elastic modulus of the conductor foil is 40 to 300 GPa, the conductor foil is less likely to break due to elongation of the wiring board. From the same viewpoint, the elastic modulus of the conductor foil may be 50 GPa or more or 280 GPa or more, and may be 60 GPa or less, or 250 GPa or less. The elastic modulus of the conductor foil here may be a value measured by a resonance method.
[0015] The conductor foil can be a metal foil. Examples of the metal foil include copper foil, titanium foil, stainless steel foil, nickel foil, permalloy foil, 42 alloy foil, kovar foil, nichrome foil, beryllium copper foil, phosphor bronze foil, brass foil, nickel silver foil, aluminum foil, tin foil, lead foil, zinc foil, solder foil, iron foil, tantalum foil, niobium foil, molybdenum foil, zirconium foil, gold foil, silver foil, palladium foil, Monel foil, Inconel foil, and Hastelloy foil. From the viewpoint of appropriate elastic modulus, the conductor foil may be selected from copper foil, gold foil, nickel foil, and iron foil. From the viewpoint of wiring formability, the conductor foil may be copper foil. Copper foil can be easily formed into a wiring pattern by photolithography without impairing the properties of the elastic resin substrate.
[0016] The copper foil is not particularly limited, and for example, electrolytic copper foil and rolled copper foil used for copper-clad laminates and flexible wiring boards can be used. Commercially available electrolytic copper foils include, for example, F0-WS-18 (manufactured by Furukawa Electric Co., Ltd., product name), NC-WS-20 (manufactured by Furukawa Electric Co., Ltd., product name), YGP-12 (manufactured by Nippon Denkai Co., Ltd., product name), GTS-18 (manufactured by Furukawa Electric Co., Ltd., product name), and F2-WS-12 (manufactured by Furukawa Electric Co., Ltd., product name). Rolled copper foils include, for example, TPC foil (manufactured by JX Metals Co., Ltd., product name), HA foil (manufactured by JX Metals Co., Ltd., product name), HA-V2 foil (manufactured by JX Metals Co., Ltd., product name), and C1100R (manufactured by Mitsui Sumitomo Metal Mining Co., Ltd., product name). Copper foils that have been subjected to roughening treatment may be used from the viewpoint of adhesion with the elastic resin layer. From the viewpoint of folding resistance, a rolled copper foil may be used.
[0017] The metal foil may have a roughened surface formed by roughening treatment. In this case, the metal foil is usually provided on the elastic resin layer with the roughened surface facing the elastic resin layer. From the viewpoint of adhesion between the elastic resin layer and the metal foil, the surface roughness Ra of the roughened surface may be 0.1 to 3 μm, or 0.2 to 2.0 μm. In order to easily form fine wiring, the surface roughness Ra of the roughened surface may be 0.3 to 1.5 μm.
[0018] The surface roughness Ra can be measured, for example, using a surface profiler Wyko NT9100 (manufactured by Veeco) under the following conditions. Measurement conditions Internal lens: 1x External lens: 50x Measurement range: 0.120 x 0.095 mm Measurement depth: 10μm Measurement method: Vertical scanning interferometry (VSI method)
[0019] The thickness of the conductor foil is not particularly limited, but may be 1 to 50 μm. When the thickness of the conductor foil is 1 μm or more, a wiring pattern can be formed more easily. When the thickness of the conductor foil is 50 μm or less, etching and handling are particularly easy.
[0020] The conductor foil is provided on one or both sides of the elastic resin layer. By providing the conductor foil on both sides of the elastic resin layer, warping due to heating for curing or the like can be suppressed.
[0021] The method for providing the conductor foil is not particularly limited, but examples thereof include a method in which a resin composition for forming an elastic resin layer is directly applied to a metal foil, and a method in which a resin composition for forming an elastic resin layer is applied to a carrier film to form a resin layer, and the formed resin layer is then laminated on the conductor foil.
[0022] The conductive plating film can be formed by a normal plating method used in the additive method or the semi-additive method. For example, after performing a plating catalyst imparting treatment to adhere palladium, the elastic resin layer is immersed in an electroless plating solution to deposit an electroless plating layer (conductive layer) having a thickness of 0.3 to 1.5 μm on the entire surface of the primer. If necessary, electrolytic plating (electrical plating) can be further performed to adjust the required thickness. As the electroless plating solution used for electroless plating, any electroless plating solution can be used, and there is no particular restriction. As for electrolytic plating, a normal method can be adopted, and there is no particular restriction. The conductive plating film (electroless plating film, electrolytic plating film) may be a copper plating film from the viewpoint of cost and resistance value.
[0023] Further, unnecessary portions are removed by etching to form a circuit layer. The etching solution used for etching can be appropriately selected depending on the type of plating. For example, when the conductor is copper plating, the etching solution used for etching can be, for example, a mixed solution of concentrated sulfuric acid and hydrogen peroxide, or a ferric chloride solution.
[0024] In order to improve the adhesive strength with the conductive plating film, the elastic resin layer may be formed with unevenness in advance. For example, the roughened surface of a copper foil may be transferred to the elastic resin layer. For example, YGP-12 (manufactured by Nippon Denkai Co., Ltd., product name), GTS-18 (manufactured by Furukawa Electric Co., Ltd., product name) or F2-WS-12 (manufactured by Furukawa Electric Co., Ltd., product name) may be used as the copper foil.
[0025] The method of transferring the roughened surface of the copper foil includes, for example, a method of directly applying a resin composition for forming an elastic resin layer to the roughened surface of the copper foil, and a method of applying a resin composition for forming an elastic resin layer to a carrier film and then molding a resin layer (elastic resin composition layer) on the copper foil. By forming a conductive plating film on both sides of the elastic resin layer, warping due to heating for curing or the like can be suppressed.
[0026] In order to improve adhesion to the conductive plating film, the elastic resin layer may be subjected to a surface treatment, such as a roughening treatment (desmear treatment), UV treatment, or plasma treatment, which are generally used in wiring board processes.
[0027] The desmear treatment may be carried out by a method used in the general manufacturing process of wiring boards, for example, an aqueous solution of sodium permanganate may be used.
[0028] The elastic resin layer can have elasticity such that the recovery rate after tensile deformation to a strain of 20% is 80% or more. This recovery rate is determined in a tensile test using a measurement sample of the elastic resin layer. The strain (displacement) applied in the first tensile test is X, and the difference between the position at which the load begins to be applied when the sample is returned to the initial position and a tensile test is performed again is Y, and R calculated by the formula: R(%)=(Y / X)×100 is defined as the recovery rate. The recovery rate can be measured with X being 20%. FIG. 1 is a stress-strain curve showing an example of the measurement of the recovery rate. From the viewpoint of resistance to repeated use, the recovery rate may be 80% or more, 85% or more, or 90% or more. The upper limit of the recovery rate by definition is 100%.
[0029] The elastic modulus (tensile modulus) of the elastic resin layer may be 0.1 MPa or more and 1000 MPa or less. When the elastic modulus is 0.1 MPa or more and 1000 MPa or less, the handleability and flexibility as a substrate tend to be particularly excellent. From this viewpoint, the elastic modulus may be 0.3 MPa or more and 100 MPa or less, or 0.5 MPa or more and 50 MPa or less.
[0030] The breaking elongation of the elastic resin layer may be 100% or more. When the breaking elongation is 100% or more, sufficient elasticity tends to be easily obtained. From this viewpoint, the breaking elongation may be 150% or more, 200% or more, 300% or more, or 500% or more. The upper limit of the breaking elongation is not particularly limited, but is usually about 1000% or less.
[0031] The elastic resin layer may contain a rubber component (A). The rubber component is mainly responsible for easily imparting elasticity to the elastic resin layer. The content of the rubber component may be 30 to 100% by mass relative to 100% by mass of the elastic resin layer.
[0032] The rubber component may contain at least one rubber selected from the group consisting of, for example, acrylic rubber, isoprene rubber, butyl rubber, styrene butadiene rubber, butadiene rubber, acrylonitrile butadiene rubber, silicone rubber, urethane rubber, chloroprene rubber, ethylene propylene rubber, fluororubber, vulcanized rubber, epichlorohydrin rubber, and chlorinated butyl rubber. From the viewpoint of protecting the wiring from damage caused by moisture absorption, etc., a rubber component with low gas permeability may be used. From this viewpoint, the rubber component may contain at least one rubber selected from styrene butadiene rubber, butadiene rubber, and butyl rubber. By using styrene butadiene rubber, the resistance of the elastic resin layer to various chemicals used in the plating process is improved, and the wiring board can be manufactured with a good yield.
[0033] Commercially available acrylic rubber products include, for example, "Nipol AR Series" from Zeon Corporation and "Clarity Series" from Kuraray Co., Ltd.
[0034] Commercially available isoprene rubber products include, for example, the "Nipol IR series" manufactured by Zeon Corporation.
[0035] Commercially available butyl rubber products include, for example, the "BUTYL series" from JSR Corporation.
[0036] Commercially available styrene butadiene rubber products include, for example, JSR Corporation's "Dynaron SEBS series" and "Dynaron HSBR series," Kraton Polymer Japan Ltd.'s "Kraton D Polymer series," and Aronkasei Corporation's "AR series."
[0037] Commercially available butadiene rubber products include, for example, the "Nipol BR series" manufactured by Zeon Corporation.
[0038] Commercially available acrylonitrile butadiene rubber products include, for example, the "JSR NBR Series" from JSR Corporation.
[0039] An example of a commercially available silicone rubber product is the "KMP series" manufactured by Shin-Etsu Silicones Co., Ltd.
[0040] Commercially available ethylene propylene rubber products include, for example, the "JSR EP Series" from JSR Corporation.
[0041] Commercially available fluororubber products include, for example, Daikin's "Dai-el Series."
[0042] Commercially available epichlorohydrin rubber products include, for example, the "Hydrin Series" manufactured by Zeon Corporation.
[0043] The rubber component can also be produced by synthesis. For example, acrylic rubber can be obtained by reacting (meth)acrylic acid, (meth)acrylic acid esters, aromatic vinyl compounds, vinyl cyanide compounds, etc.
[0044] The rubber component may contain a rubber having a crosslinking group. The use of a rubber having a crosslinking group tends to improve the heat resistance of the elastic resin layer. The crosslinking group may be a reactive group capable of proceeding with a reaction that crosslinks the molecular chains of the rubber component. Examples of the crosslinking group include the reactive group, acid anhydride group, amino group, hydroxyl group, epoxy group, and carboxyl group of the (B) crosslinking component described later.
[0045] The rubber component may contain a rubber having at least one crosslinking group of an acid anhydride group or a carboxyl group. An example of a rubber having an acid anhydride group is a rubber partially modified with maleic anhydride. The rubber partially modified with maleic anhydride is a polymer containing a structural unit derived from maleic anhydride. An example of a commercially available product of a rubber partially modified with maleic anhydride is a styrene-based elastomer "Tufprene 912" manufactured by Asahi Kasei Corporation.
[0046] The rubber partially modified with maleic anhydride may be a hydrogenated styrene-based elastomer partially modified with maleic anhydride. Hydrogenated styrene-based elastomers are also expected to have effects such as improved weather resistance. Hydrogenated styrene-based elastomers are elastomers obtained by adding hydrogen to the unsaturated double bonds of a styrene-based elastomer having a soft segment containing an unsaturated double bond. Examples of commercially available hydrogenated styrene-based elastomers partially modified with maleic anhydride include "FG1901" and "FG1924" from Kraton Polymer Japan Co., Ltd., and "Tuftec M1911", "Tuftec M1913", and "Tuftec M1943" from Asahi Kasei Corporation.
[0047] From the viewpoint of coating properties, the weight average molecular weight of the rubber component may be 20000 to 200000, 30000 to 150000, or 50000 to 125000. The weight average molecular weight (Mw) here means a standard polystyrene equivalent value determined by gel permeation chromatography (GPC).
[0048] The elastic resin layer may be a cured product of a resin composition containing (A) a rubber component. In this case, a curable resin composition is used as the resin composition for forming the elastic resin layer. This curable resin composition may further contain, for example, (B) a crosslinking component. That is, the elastic resin layer may further contain a crosslinked polymer of (B) the crosslinking component. The crosslinking component may be, for example, a compound having at least one reactive group selected from the group consisting of (meth)acrylic groups, vinyl groups, epoxy groups, styryl groups, amino groups, isocyanurate groups, ureido groups, cyanate groups, isocyanate groups, mercapto groups, hydroxyl groups, and carboxyl groups, and a cured product containing a crosslinked polymer can be formed by the reaction of these reactive groups. From the viewpoint of improving the heat resistance of the elastic resin layer, the crosslinking component may be a compound having a reactive group selected from epoxy groups, amino groups, hydroxyl groups, and carboxyl groups. These compounds can be used alone or in combination of two or more types.
[0049] Examples of compounds having a (meth)acrylic group include (meth)acrylate compounds. The (meth)acrylate compounds may be monofunctional, bifunctional, or polyfunctional, and are not particularly limited, but may be bifunctional or polyfunctional (meth)acrylates in order to obtain sufficient curability.
[0050] Examples of monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, butoxyethyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octylheptyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and the like. aliphatic (meth)acrylates such as acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolypropylene glycol (meth)acrylate, mono(2-(meth)acryloyloxyethyl)succinate; alicyclic (meth)acrylates such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, isobornyl (meth)acrylate, mono(2-(meth)acryloyloxyethyl)tetrahydrophthalate, mono(2-(meth)acryloyloxyethyl)hexahydrophthalate;Benzyl (meth)acrylate, phenyl (meth)acrylate, o-biphenyl (meth)acrylate, 1-naphthyl (meth)acrylate, 2-naphthyl (meth)acrylate, phenoxyethyl (meth)acrylate, p-cumylphenoxyethyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, 1-naphthoxyethyl (meth)acrylate, 2-naphthoxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate, phenoxypolypropylene glycol (meth)acrylate aromatic (meth)acrylates such as 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxy-3-(o-phenylphenoxy)propyl (meth)acrylate, 2-hydroxy-3-(1-naphthoxy)propyl (meth)acrylate, and 2-hydroxy-3-(2-naphthoxy)propyl (meth)acrylate; heterocyclic (meth)acrylates such as 2-tetrahydrofurfuryl (meth)acrylate, N-(meth)acryloyloxyethylhexahydrophthalimide, and 2-(meth)acryloyloxyethyl-N-carbazole, and caprolactone-modified versions of these. Among these, monofunctional (meth)acrylates may be selected from the above aliphatic (meth)acrylates and aromatic (meth)acrylates from the viewpoints of compatibility with styrene-based elastomers, transparency, and heat resistance.
[0051] Examples of bifunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, and 1,3-butanediol. aliphatic (meth)acrylates such as butyl di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, glycerin di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, and ethoxylated 2-methyl-1,3-propanediol di(meth)acrylate;Cyclohexane dimethanol (meth)acrylate, ethoxylated cyclohexane dimethanol (meth)acrylate, propoxylated cyclohexane dimethanol (meth)acrylate, ethoxylated propoxylated cyclohexane dimethanol (meth)acrylate, tricyclodecane dimethanol (meth)acrylate, ethoxylated tricyclodecane dimethanol (meth)acrylate, propoxylated tricyclodecane dimethanol (meth)acrylate, ethoxylated propoxylated tricyclodecane dimethanol (meth)acrylate ) acrylate, ethoxylated hydrogenated bisphenol A di(meth)acrylate, propoxylated hydrogenated bisphenol A di(meth)acrylate, ethoxylated propoxylated hydrogenated bisphenol A di(meth)acrylate, ethoxylated hydrogenated bisphenol F di(meth)acrylate, propoxylated hydrogenated bisphenol F di(meth)acrylate, ethoxylated propoxylated hydrogenated bisphenol F di(meth)acrylate and other alicyclic (meth)acrylates; ethoxylated bisphenol A di(meth)acrylate, propoxylated bis Phenol A di(meth)acrylate, ethoxylated propoxylated bisphenol A di(meth)acrylate, ethoxylated bisphenol F di(meth)acrylate, propoxylated bisphenol F di(meth)acrylate, ethoxylated propoxylated bisphenol F di(meth)acrylate, ethoxylated bisphenol AF di(meth)acrylate, propoxylated bisphenol AF di(meth)acrylate, ethoxylated propoxylated bisphenol AF di(meth)acrylate, ethoxylated fluorene di(meth)acrylate aromatic (meth)acrylates such as acrylates, propoxylated fluorene type di(meth)acrylates, and ethoxylated propoxylated fluorene type di(meth)acrylates; heterocyclic (meth)acrylates such as ethoxylated isocyanuric acid di(meth)acrylates, propoxylated isocyanuric acid di(meth)acrylates, and ethoxylated propoxylated isocyanuric acid di(meth)acrylates; caprolactone modified versions of these; aliphatic epoxy (meth)acrylates such as neopentyl glycol type epoxy (meth)acrylates;Examples of the epoxy (meth)acrylate include cycloaliphatic epoxy (meth)acrylates such as cyclohexane dimethanol type epoxy (meth)acrylate, hydrogenated bisphenol A type epoxy (meth)acrylate, and hydrogenated bisphenol F type epoxy (meth)acrylate; and aromatic epoxy (meth)acrylates such as resorcinol type epoxy (meth)acrylate, bisphenol A type epoxy (meth)acrylate, bisphenol F type epoxy (meth)acrylate, bisphenol AF type epoxy (meth)acrylate, and fluorene type epoxy (meth)acrylate. Among these, bifunctional (meth)acrylates may be selected from the above aliphatic (meth)acrylates and aromatic (meth)acrylates from the viewpoints of compatibility with styrene-based elastomers, transparency, and heat resistance.
[0052] Examples of the polyfunctional (meth)acrylate having three or more functional groups include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, ethoxylated propoxylated trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, ethoxylated propoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tri ... Examples of the polyfunctional (meth)acrylate include aliphatic (meth)acrylates such as silyl pentaerythritol tetra(meth)acrylate, ethoxylated propoxylated pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetraacrylate, and dipentaerythritol hexa(meth)acrylate; heterocyclic (meth)acrylates such as ethoxylated isocyanuric acid tri(meth)acrylate, propoxylated isocyanuric acid tri(meth)acrylate, and ethoxylated propoxylated isocyanuric acid tri(meth)acrylate; caprolactone-modified versions of these; and aromatic epoxy (meth)acrylates such as phenol novolac epoxy (meth)acrylate and cresol novolac epoxy (meth)acrylate. Among these, polyfunctional (meth)acrylates may be selected from the above aliphatic (meth)acrylates and aromatic (meth)acrylates from the viewpoints of compatibility with styrene-based elastomers, transparency, and heat resistance.
[0053] The combination of a rubber having a maleic anhydride group or a carboxyl group and a compound having an epoxy group (epoxy resin) provides particularly excellent effects in terms of the heat resistance and low moisture permeability of the elastic resin layer, the adhesion between the elastic resin layer and the conductive layer, and the low tack of the cured resin layer. When the heat resistance of the elastic resin layer is improved, the deterioration of the elastic resin layer in a heating process such as nitrogen reflow can be suppressed. When the cured resin layer has low tack, the conductor board or wiring board can be handled with good workability.
[0054] The compound containing an epoxy group is not particularly limited as long as it has an epoxy group in the molecule, and can be, for example, a general epoxy resin. The epoxy resin may be monofunctional, bifunctional, or polyfunctional, and is not particularly limited, but a bifunctional or polyfunctional epoxy resin may be used to obtain sufficient curability.
[0055] Examples of epoxy resins include bisphenol A type, bisphenol F type, phenol novolac type, naphthalene type, dicyclopentadiene type, and cresol novolac type. Epoxy resins modified with an aliphatic chain can impart flexibility. An example of a commercially available aliphatic chain modified epoxy resin is EXA-4816 manufactured by DIC Corporation. From the viewpoints of curability, low tackiness, and heat resistance, phenol novolac type, cresol novolac type, naphthalene type, or dicyclopentadiene type epoxy resins may be selected. These epoxy resins may be used alone or in combination of two or more types.
[0056] The content of the crosslinked polymer formed from the crosslinking component may be 10 to 50% by mass based on the mass of the elastic resin layer. If the content of the crosslinked polymer formed from the crosslinking component is within the above range, the adhesive strength with the conductor foil or conductor plating film tends to be improved while maintaining the properties of the elastic resin layer. From the above viewpoints, the content of the crosslinked polymer formed from the crosslinking component may be 15 to 40% by mass. The content of the crosslinking component in the resin composition for forming the elastic resin layer may be within these ranges.
[0057] The elastic resin layer or the resin composition used to form the elastic resin layer may further contain an additive as a component (C). The additive (C) may be at least one of a curing agent or a curing accelerator. The curing agent is a compound that is involved in the curing reaction itself, and the curing accelerator is a compound that functions as a catalyst for the curing reaction. A compound having both the functions of a curing agent and a curing accelerator may also be used. The curing agent may be a polymerization initiator. These can be appropriately selected according to the other components contained in the resin composition. For example, if the resin composition contains a (meth)acrylate compound or the like, a polymerization initiator may be added. There is no particular limit to the polymerization initiator as long as it initiates polymerization by heating or irradiation with ultraviolet light or the like, and for example, a thermal radical polymerization initiator or a photoradical polymerization initiator can be used. The thermal radical initiator is easy to uniformly proceed with the reaction of the resin composition. The photoradical initiator is advantageous in that it can be cured at room temperature, preventing deterioration of the device due to heat, and suppressing warping of the elastic resin layer.
[0058] Examples of the thermal radical polymerization initiator include ketone peroxides such as methyl ethyl ketone peroxide, cyclohexanone peroxide, and methylcyclohexanone peroxide; 1,1-bis(t-butylperoxy)cyclohexane, 1,1-bis(t-butylperoxy)-2-methylcyclohexane, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, and 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane. Peroxyketals such as cyclohexane; hydroperoxides such as p-menthane hydroperoxide; dialkyl peroxides such as α,α'-bis(t-butylperoxy)diisopropylbenzene, dicumyl peroxide, t-butylcumyl peroxide, and di-t-butyl peroxide; diacyl peroxides such as octanoyl peroxide, lauroyl peroxide, stearyl peroxide, and benzoyl peroxide; bis(4-t-butylcyclohexyl) peroxydicarbonate, di-2-ethoxyethyl peroxycarbonates such as di-2-ethylhexyl peroxydicarbonate, di-3-methoxybutyl peroxycarbonate; t-butyl peroxypivalate, t-hexyl peroxypivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, t-hexyl peroxy-2-ethylhexanoate, t-butyl peroxy-2-ethylhexanoate, t-butyl peroxyesters such as peroxyisobutyrate, t-hexylperoxyisopropyl monocarbonate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurylate, t-butylperoxyisopropyl monocarbonate, t-butylperoxy-2-ethylhexyl monocarbonate, t-butylperoxybenzoate, t-hexylperoxybenzoate, 2,5-dimethyl-2,5-bis(benzoylperoxy)hexane, and t-butylperoxyacetate;Examples of the thermal radical polymerization initiator include azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(4-methoxy-2'-dimethylvaleronitrile). Among these, the thermal radical polymerization initiator may be selected from the above diacyl peroxides, the above peroxy esters, and the above azo compounds from the viewpoints of curability, transparency, and heat resistance.
[0059] Examples of the photoradical polymerization initiator include benzoin ketals such as 2,2-dimethoxy-1,2-diphenylethan-1-one; α-hydroxyketones such as 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, and 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one; 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, and 1,2-methyl-1-[4-(methylthio)phenyl] α-Aminoketones such as 1-[(4-phenylthio)phenyl]-1,2-octadione-2-(benzoyl)oxime; phosphine oxides such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-( 2,4,5-triarylimidazole dimers such as 2-(o-chlorophenyl)-4,5-di(methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-diphenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer; benzophenone, N,N,N',N'-tetramethyl-4,4'-diaminobenzophenone, N,N''-tetraethyl-4,4'-diaminobenzophenone, 4-methoxy- Benzophenone compounds such as 4'-dimethylaminobenzophenone; quinone compounds such as 2-ethylanthraquinone, phenanthrenequinone, 2-tert-butylanthraquinone, octamethylanthraquinone, 1,2-benzanthraquinone, 2,3-benzanthraquinone, 2-phenylanthraquinone, 2,3-diphenylanthraquinone, 1-chloroanthraquinone, 2-methylanthraquinone, 1,4-naphthoquinone, 9,10-phenanthraquinone, 2-methyl-1,4-naphthoquinone, and 2,3-dimethylanthraquinone;Benzoin ethers such as benzoin methyl ether, benzoin ethyl ether, and benzoin phenyl ether; benzoin compounds such as benzoin, methylbenzoin, and ethylbenzoin; benzyl compounds such as benzyl dimethyl ketal; acridine compounds such as 9-phenylacridine and 1,7-bis(9,9'-acridinylheptane); N-phenylglycine, coumarin, and the like;
[0060] In the 2,4,5-triarylimidazole dimer, the substituents of the aryl groups of the two triarylimidazole moieties may be the same to give a symmetrical compound, or different to give an asymmetrical compound. A thioxanthone compound may be combined with a tertiary amine, such as the combination of diethylthioxanthone and dimethylaminobenzoic acid.
[0061] Among these, the photoradical polymerization initiator may be selected from the above-mentioned α-hydroxyketone and the above-mentioned phosphine oxide in terms of curability, transparency, and heat resistance. These thermal and photoradical polymerization initiators may be used alone or in combination of two or more. Furthermore, they may be combined with an appropriate sensitizer.
[0062] When the curable resin composition for forming the elastic resin layer contains (A) a rubber component, (B) a crosslinking component, and (C) a curing agent as the component, the content of the curing agent (or polymerization initiator) may be 0.1 to 10 parts by mass relative to 100 parts by mass of the total amount of the rubber component and the crosslinking component. When the content of the curing agent (or polymerization initiator) is 0.1 parts by mass or more, sufficient curing tends to be easily obtained. When the content of the curing agent (or polymerization initiator) is 10 parts by mass or less, sufficient light transmittance tends to be easily obtained. From the above viewpoints, the content of the curing agent (or polymerization initiator) may be 0.3 to 7 parts by mass, or 0.5 to 5 parts by mass.
[0063] The curing agent may contain at least one selected from the group consisting of aliphatic polyamines, polyaminoamides, polymercaptans, aromatic polyamines, acid anhydrides, carboxylic acids, phenol novolac resins, ester resins, and dicyandiamide. These curing agents can be combined with, for example, a compound having an epoxy group (epoxy resin).
[0064] A curing accelerator selected from tertiary amines, imidazoles, acid anhydrides, and phosphines may be added as component (C) to the resin composition containing the epoxy resin. From the viewpoint of storage stability and curing properties of the varnish, imidazole may be used. When the rubber component contains a rubber partially modified with maleic anhydride, an imidazole compatible with the rubber may be selected.
[0065] When the resin composition for forming the elastic resin layer contains (A) a rubber component and (B) a crosslinking component, the content of imidazole may be 0.1 to 10 parts by mass relative to 100 parts by mass of the total amount of the rubber component and the crosslinking component. When the content of imidazole is 0.1 parts by mass or more, sufficient curing tends to be easily obtained. When the content of imidazole is 10 parts by mass or less, sufficient heat resistance tends to be easily obtained. From the above viewpoints, the content of imidazole may be 0.3 to 7 parts by mass, or 0.5 to 5 parts by mass.
[0066] When the resin composition for forming the elastic resin layer contains (A) a rubber component, (B) a crosslinking component, and (C) an additive, the content of the rubber component may be 30 to 98 mass%, 50 to 97 mass%, or 60 to 95 mass% based on the total amount of the (A) rubber component, (B) a crosslinking component, and (C) component. When the content of the rubber component is 30 mass% or more, sufficient elasticity is easily obtained. When the content of the rubber component is 98 mass% or less, the elastic resin layer tends to have particularly excellent properties in terms of adhesion, insulation reliability, and heat resistance.
[0067] In addition to the above components, the elastic resin layer or the resin composition for forming the elastic resin layer may further contain, as necessary, antioxidants, anti-yellowing agents, ultraviolet absorbers, visible light absorbers, colorants, plasticizers, stabilizers, fillers, flame retardants, leveling agents, etc., within a range that does not significantly impair the effects of the present invention.
[0068] In particular, the elastic resin layer or the resin composition for forming the elastic resin layer may contain at least one deterioration inhibitor selected from the group consisting of an antioxidant, a heat stabilizer, a light stabilizer, and a hydrolysis inhibitor. The antioxidant suppresses deterioration due to oxidation. In addition, the antioxidant imparts sufficient heat resistance at high temperatures to the elastic resin layer. The heat stabilizer imparts stability at high temperatures to the elastic resin layer. Examples of light stabilizers include ultraviolet absorbers that prevent deterioration due to ultraviolet rays, light blocking agents that block light, and quenchers that have a quenching function that receives light energy absorbed by an organic material and stabilizes the organic material. The hydrolysis inhibitor suppresses deterioration due to moisture. The deterioration inhibitor may be at least one selected from the group consisting of an antioxidant, a heat stabilizer, and an ultraviolet absorber. As the deterioration inhibitor, only one of the components exemplified above may be used, or two or more may be used in combination. In order to obtain a better effect, two or more deterioration inhibitors may be used in combination.
[0069] The antioxidant may be, for example, one or more selected from the group consisting of phenol-based antioxidants, amine-based antioxidants, sulfur-based antioxidants, and phosphite-based antioxidants. In order to obtain a more excellent effect, two or more antioxidants may be used in combination. A phenol-based antioxidant and a sulfur-based antioxidant may be used in combination.
[0070] The phenolic antioxidant may be a compound having a substituent with large steric hindrance such as a tertiary butyl group or a trimethylsilyl group at the ortho position of the phenolic hydroxyl group. The phenolic antioxidant is also called a hindered phenolic antioxidant.
[0071] The phenolic antioxidant may be, for example, one or more compounds selected from the group consisting of 2-t-butyl-4-methoxyphenol, 3-t-butyl-4-methoxyphenol, 2,6-di-t-butyl-4-ethylphenol, 2,2'-methylene-bis(4-methyl-6-t-butylphenol), 4,4'-thiobis-(3-methyl-6-t-butylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, and tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. The phenolic antioxidant may be a polymeric phenolic antioxidant typified by 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene and tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane.
[0072] Examples of the phosphite antioxidant include triphenyl phosphite, diphenyl isodecyl phosphite, phenyl diisodecyl phosphite, 4,4'-butylidene-bis(3-methyl-6-t-butylphenyl ditridecyl) phosphite, cyclic neopentane tetrayl bis(nonylphenyl) phosphite, cyclic neopentane tetrayl bis(dinonylphenyl) phosphite, cyclic neopentane tetrayl tris(nonylphenyl) phosphite, and cyclic neopentane tetrayl tris(nonylphenyl) phosphite. The compound may be one or more compounds selected from the group consisting of diisodecyl tris(dinonylphenyl)phosphite, 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, 2,2-methylenedibis(4,6-di-t-butylphenyl)-2-ethylhexyl phosphite, diisodecyl pentaerythritol diphosphite and tris(2,4-di-t-butylphenyl)phosphite, or may be tris(2,4-di-t-butylphenyl)phosphite.
[0073] Other examples of antioxidants include hydroxylamine-based antioxidants such as N-methyl-2-dimethylaminoacetohydroxamic acid, and sulfur-based antioxidants such as dilauryl 3,3'-thiodipropionate.
[0074] The content of the antioxidant may be 0.1 to 20% by mass based on the mass of the elastic resin layer or the resin composition for forming the elastic resin layer. When the content of the antioxidant is 0.1 parts by weight or more, the elastic resin layer is likely to have sufficient heat resistance. When the content of the antioxidant is 20 parts by weight or less, bleeding and blooming can be suppressed.
[0075] From the viewpoint of preventing sublimation during heating, the molecular weight of the antioxidant may be 400 or more, 600 or more, or 750 or more. When two or more types of antioxidants are contained, the average of their molecular weights may be in the above range.
[0076] Heat stabilizers (thermal degradation inhibitors) include metal soaps or inorganic acid salts, such as combinations of zinc and barium salts of higher fatty acids, organotin compounds, such as organotin maleates and organotin mercaptos, and fullerenes (e.g., fullerene hydroxide).
[0077] Examples of ultraviolet absorbers include benzophenone-based ultraviolet absorbers such as 2,4-dihydroxybenzophenone, benzotriazole-based ultraviolet absorbers such as 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and cyanoacrylate-based ultraviolet absorbers such as 2-ethylhexyl-2-cyano-3,3'-diphenylacrylate.
[0078] Examples of the hydrolysis inhibitor include carbodiimide derivatives, epoxy compounds, isocyanate compounds, acid anhydrides, oxazoline compounds, and melamine compounds.
[0079] Examples of other deterioration inhibitors include hindered amine light stabilizers, ascorbic acid, propyl gallate, catechin, oxalic acid, malonic acid, and phosphorous esters.
[0080] The elastic resin layer can be produced, for example, by a method including dissolving or dispersing a rubber component and, if necessary, other components in an organic solvent to obtain a resin varnish, and forming a film of the resin varnish on a conductor foil or a carrier film by a method described below.
[0081] The organic solvent used here is not particularly limited, and examples thereof include aromatic hydrocarbons such as toluene, xylene, mesitylene, cumene, and p-cymene; cyclic ethers such as tetrahydrofuran and 1,4-dioxane; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, and 4-hydroxy-4-methyl-2-pentanone; esters such as methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, and γ-butyrolactone; carbonates such as ethylene carbonate and propylene carbonate; and amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone. From the viewpoint of solubility and boiling point, toluene or N,N-dimethylacetamide may be used. These organic solvents may be used alone or in combination of two or more kinds. The solid content (components other than organic solvent) concentration in the resin varnish may be 20 to 80 mass%.
[0082] The carrier film is not particularly limited, and examples thereof include polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate; polyolefins such as polyethylene and polypropylene; polycarbonate, polyamide, polyimide, polyamideimide, polyetherimide, polyethersulfide, polyethersulfone, polyetherketone, polyphenylene ether, polyphenylene sulfide, polyarylate, polysulfone, and liquid crystal polymers. Among these, from the viewpoint of flexibility and toughness, films of polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polypropylene, polycarbonate, polyamide, polyimide, polyamideimide, polyphenylene ether, polyphenylene sulfide, polyarylate, or polysulfone may be used as the carrier film.
[0083] The thickness of the carrier film is not particularly limited, but may be 3 to 250 μm. When the thickness of the carrier film is 3 μm or more, the film strength is sufficient, and when the thickness of the carrier film is 250 μm or less, sufficient flexibility is obtained. From the above viewpoints, the thickness may be 5 to 200 μm, or 7 to 150 μm. From the viewpoint of improving the peelability from the elastic resin layer, a film in which a release treatment is performed on the base film with a silicone-based compound, a fluorine-containing compound, or the like may be used as necessary.
[0084] If necessary, a protective film may be attached onto the elastic resin layer to form a laminated film having a three-layer structure consisting of a conductor foil or carrier film, an elastic resin layer, and a protective film.
[0085] The protective film is not particularly limited, and examples thereof include polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; and polyolefins such as polyethylene and polypropylene. Among these, from the viewpoint of flexibility and toughness, a film of polyester such as polyethylene terephthalate, or polyolefin such as polyethylene or polypropylene may be used as the protective film. From the viewpoint of improving the peelability from the elastic resin layer, the protective film may be subjected to a release treatment using a silicone-based compound, a fluorine-containing compound, or the like.
[0086] The thickness of the protective film may be appropriately changed depending on the desired flexibility, but may be 10 to 250 μm. If the thickness is 10 μm or more, the film strength tends to be sufficient, and if it is 250 μm or less, sufficient flexibility tends to be obtained. From the above viewpoints, the thickness may be 15 to 200 μm, or 20 to 150 μm.
[0087] A wiring board having a conductor foil according to one embodiment can be manufactured by a method including, for example, a step of preparing a laminate (conductor board) having an elastic resin layer and a conductor foil laminated on the elastic resin layer, a step of forming an etching resist on the conductor foil, a step of exposing the etching resist and developing the exposed etching resist to form a resist pattern that covers a portion of the conductor foil, a step of removing a portion of the conductor film that is not covered by the resist pattern, and a step of removing the resist pattern.
[0088] Any method may be used to obtain a laminate (conductor substrate) having an elastic resin layer and a conductor foil, and examples of such methods include a method of applying a varnish of a resin composition for forming an elastic resin layer to a conductor foil, and a method of laminating a conductor foil to an elastic resin layer formed on a carrier film using a vacuum press, a laminator, etc. When the resin composition for forming the elastic resin layer contains a crosslinking component, the elastic resin layer is formed by proceeding with a crosslinking reaction (curing reaction) of the crosslinking component by heating or light irradiation.
[0089] The method for laminating the elastic resin layer on the carrier film onto the conductor foil may be any method, but may be a roll laminator, a vacuum laminator, a vacuum press, etc. From the viewpoint of production efficiency, molding may be performed using a roll laminator or a vacuum laminator.
[0090] The thickness of the elastic resin layer after drying is not particularly limited, but is usually 5 to 1000 μm. Within this range, sufficient strength of the elastic substrate is easily obtained, and drying can be performed sufficiently, so that the amount of residual solvent in the resin film can be reduced.
[0091] A laminate having conductor foils formed on both sides of the elastic resin layer may be produced by further laminating a conductor foil on the side opposite to the conductor foil of the elastic resin layer. By providing conductor layers on both sides of the elastic resin layer, warping of the laminate during curing can be suppressed.
[0092] A method for forming a wiring pattern on the conductor foil of a laminate (a laminate for forming a wiring board) generally uses a method using etching, etc. For example, when a copper foil is used as the conductor foil, an etching solution that can be used is, for example, a mixed solution of concentrated sulfuric acid and hydrogen peroxide, or a ferric chloride solution.
[0093] Examples of the etching resist used in the etching include Photec H-7025 (trade name, manufactured by Hitachi Chemical Co., Ltd.), Photec H-7030 (trade name, manufactured by Hitachi Chemical Co., Ltd.), and X-87 (trade name, manufactured by Taiyo Holdings Co., Ltd.). The etching resist is usually removed after the wiring pattern is formed.
[0094] One embodiment of a method for manufacturing a wiring board having a conductor plating film includes the steps of forming a conductor plating film on an elastic resin layer by electroless plating, forming a plating resist on the conductor plating film, exposing the plating resist and developing the exposed plating resist to form a resist pattern that covers a portion of the elastic resin layer, forming a further conductor plating film by electrolytic plating on the conductor plating film in the portion not covered by the resist pattern, removing the resist pattern, and removing the portion of the conductor plating film formed by electroless plating that is not covered by the conductor plating film formed by electrolytic plating.
[0095] Yet another embodiment of the method for manufacturing a wiring board includes a step of forming an etching resist on a conductive plating film formed on an elastic resin layer, a step of exposing the etching resist and developing the exposed etching resist to form a resist pattern that covers a portion of the elastic resin layer, a step of removing the conductive plating film from a portion not covered by the resist pattern, and a step of removing the resist pattern.
[0096] Examples of plating resists used as plating masks include Photec RY3325 (Hitachi Chemical's product name), Photec RY-5319 (Hitachi Chemical's product name), and MA-830 (Taiyo Holdings Co., Ltd.'s product name). Details of electroless plating and electrolytic plating are as described above.
[0097] By mounting various electronic elements on the wiring board, a stretchable device can be obtained. EXAMPLES
[0098] The present invention will be described in more detail with reference to the following examples, although the present invention is not limited to these examples.
[0099] Study 1 1-1. Preparation of varnish for forming elastic resin layer [Resin varnish A] Resin varnish A was obtained by mixing 30 g of hydrogenated styrene-butadiene rubber (manufactured by Asahi Kasei Corporation, product name Tuftec P1500) as component (A) and 70 g of toluene with stirring. [Resin varnish B] 20 g of hydrogenated styrene butadiene rubber (Dynaron 2324P, product name, manufactured by JSR Corporation) as component (A), 5 g of butanediol acrylate (Fancryl FA-124AS, product name, manufactured by Hitachi Chemical Co., Ltd.) as component (B), and 0.4 g of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Irgacure 819, product name, manufactured by BASF Ltd.) as component (C) were mixed with stirring with 15 g of toluene as a solvent to obtain resin varnish B. [Resin varnish C] 20 g of an acrylic polymer (product name: Clarity LA2140, manufactured by Kuraray Co., Ltd.) as component (A), 5 g of an aliphatic chain-modified epoxy resin (product name: EXA4816, manufactured by DIC Corporation) as component (B), and 0.5 g of 2-phenylimidazole (product name: 2PZ, manufactured by Shikoku Kasei Co., Ltd.) as component (C) were mixed with stirring with 15 g of methyl ethyl ketone as a solvent to obtain resin varnish C. [Resin varnish D] 25.0 g of methyl ethyl ketone was mixed with 50 g of biphenyl aralkyl type epoxy resin (product name: NC-3000H, manufactured by Nippon Kayaku Co., Ltd.). 20 g of phenol novolac type phenolic resin (product name: TD2131, manufactured by DIC Corporation) was added thereto, and 0.15 g of 2-phenylimidazole (product name: 2PZ, manufactured by Shikoku Kasei Kogyo Co., Ltd.) was further added as a curing accelerator. The mixture was then diluted with methyl ethyl ketone to obtain resin varnish D.
[0100] 1-2. Preparation of laminate with conductor layer Example 1-1 [Laminated film with elastic resin layer] A release-treated polyethylene terephthalate (PET) film (Teijin DuPont Films Co., Ltd., "Purex A31", thickness 25 μm) was prepared as a carrier film. Resin varnish A was applied to the release-treated surface of this PET film using a knife coater (Yasui Seiki Co., Ltd., "SNC-350"). The coating was dried in a dryer (Futaba Scientific Co., Ltd., "MSO-80TPS") at 100°C for 20 minutes to form an elastic resin layer with a thickness of 100 μm after coating. A release-treated PET film with the same release treatment as the carrier film was attached as a protective film to the formed elastic resin layer with the release-treated surface facing the elastic resin layer, to obtain laminated film A. [Laminate with conductor layer] The protective film of laminate film A was peeled off, and the elastic resin layer of laminate film A was placed on the roughened surface of copper foil (manufactured by Nippon Denkai Co., Ltd., product name YGP-12). Using a vacuum pressure laminator (Nichigo-Morton Co., Ltd., "V130"), the two were pressed together under conditions of a pressure of 0.5 MPa, a temperature of 90°C, and a pressing time of 60 seconds to produce a laminate with a conductor layer.
[0101] Example 1-2 A laminate having a copper foil and an uncured resin layer was obtained in the same manner as in Example 1-1, except that the resin varnish A was changed to resin varnish B and the copper foil was changed to (BHY-82F-HA-V2-12 μm, product name, manufactured by JX Metals Corporation). Then, ultraviolet light (wavelength 365 nm) was applied at 2000 mJ / cm using an ultraviolet exposure machine (Mikasa Co., Ltd. "ML-320FSAT"). 2 The resin layer was cured by irradiation to obtain a laminate with a conductor layer.
[0102] Examples 1-3 A laminate having a copper foil and an uncured resin layer was obtained in the same manner as in Example 1-1, except that the resin varnish A was changed to the resin varnish C. Thereafter, the resin layer was cured using a dryer at 180° C. for 1 hour, to obtain a laminate with a conductor layer.
[0103] Comparative Example 1-1 A laminate having a copper foil and an uncured resin layer was obtained in the same manner as in Example 1-1, except that the resin varnish A was changed to the resin varnish D. Thereafter, the resin layer was cured using a dryer at 180° C. for 1 hour, to obtain a laminate with a conductor layer.
[0104] [Fabrication and evaluation of wiring boards] As shown in FIG. 2, a test wiring board 1 was produced having an elastic resin layer 3 and a conductor foil having a wave pattern formed on the elastic resin layer 3 as a conductor layer 5. First, an etching resist (Hitachi Chemical Co., Ltd., Photec RY-5325, product name) was attached to the conductor layer of each conductor layer-attached laminate using a roll laminator, and a phototool with a wave pattern formed thereon was attached to the etching resist. The etching resist was exposed to light at 50 mJ / cm using an EXM-1201 exposure machine manufactured by Oak Manufacturing Co., Ltd. 2 The etching resist was exposed to light with an energy of 1000 W. Then, spray development was performed for 240 seconds with a 1 wt % sodium carbonate aqueous solution at 30° C. to dissolve the unexposed parts of the etching resist and form a resist pattern with a wavy opening. Next, the copper foil in the part not covered by the resist pattern was removed with an etching solution. After that, the etching resist was removed with a stripping solution to obtain a wiring board 1 having a conductor foil 5 on an elastic resin layer 3, the conductor foil 5 forming a wavy wiring pattern with a wiring width of 50 μm and meandering along a predetermined direction X. The obtained wiring board was tensile deformed to a strain of 10% in the X direction and then returned to its original state, and the elastic resin layer and the corrugated wiring pattern were observed. The elastic resin layer and the wiring pattern were rated as "A" if they did not break when stretched, and "C" if they did break.
[0105] [Table 1]
[0106] The evaluation results of Examples 1-1 to 1-3 and Comparative Example 1-1 are shown in Table 1. It was found that in the wiring boards having a corrugated wiring pattern formed by the conductor layer-attached laminates of Examples 1-1 to 1-3, the elastic resin layer did not break even at 10% elongation, and the appearance of the corrugated wiring pattern was also satisfactory. On the other hand, in Comparative Example 1-1, since the resin layer had no elasticity, it broke before 10% elongation, and the wiring also broke at the same time.
[0107] Study 2 Example 2-1 [Resin varnish] A resin varnish was obtained by mixing with stirring 10 g of maleic anhydride-modified styrene-ethylene-butadiene rubber (FG1924GT, product name, manufactured by KRATON Corporation) as component (A), 2.5 g of dicyclopentadiene-type epoxy resin (EPICLON HP7200H, product name, manufactured by DIC Corporation) as component (B), and 0.38 g of 1-benzyl-2-methylimidazole (1B2MZ, product name, manufactured by Shikoku Kasei Corporation) as component (C) (curing accelerator).
[0108] [Laminated film] A release-treated polyethylene terephthalate (PET) film (Teijin DuPont Films Co., Ltd., "Purex A31", thickness 25 μm) was prepared as a carrier film. The above-mentioned resin varnish was applied to the release-treated surface of this PET film using a knife coater (Yasui Seiki Co., Ltd., "SNC-350"). The coating was dried by heating at 100°C for 20 minutes in a dryer (Futaba Scientific Co., Ltd., "MSO-80TPS") to form a resin layer with a thickness of 100 μm. A release-treated PET film with the same release treatment as the carrier film was attached as a protective film to the formed resin layer with the release-treated surface facing the resin layer, to obtain a laminated film.
[0109] [Preparation of conductive substrate] The protective film of the laminated film was peeled off, and an electrolytic copper foil (F2-WS-12, product name, manufactured by Furukawa Electric Co., Ltd.) with a roughened surface with a surface roughness of 1.5 μm Ra was placed on the exposed resin layer with the roughened surface facing the resin layer. In this state, the electrolytic copper foil was laminated to the resin layer using a vacuum pressure laminator (Nikko Materials Co., Ltd. "V130") under conditions of a pressure of 0.5 MPa, a temperature of 90°C, and a pressure time of 60 seconds. After that, the laminate was heated at 180°C for 60 minutes in a dryer (Futaba Scientific Co., Ltd. "MSO-80TPS") to obtain a conductive substrate having an elastic resin layer, which is a cured product of the resin layer, and an electrolytic copper foil.
[0110] Example 2-2 10 g of maleic anhydride-modified styrene-ethylene-butadiene rubber (KRATON Corporation, FG1924GT, product name) as component (A), 2.5 g of dicyclopentadiene-type epoxy resin (DIC Corporation, EPICLON HP7200H, product name) as component (B), 0.38 g of 1-benzyl-2-methylimidazole (Shikoku Kasei Corporation, 1B2MZ, product name) as component (C) (curing accelerator), 0.1 g of a phenol-based antioxidant (ADEKA Corporation, AO-60, product name), and 0.1 g of a phosphite antioxidant (ADEKA Corporation, 2112, product name) were mixed with 50 g of toluene while stirring to obtain a resin varnish. Using the obtained resin varnish, a laminated film having a resin layer and a conductive substrate were produced in the same manner as in Example 2-1.
[0111] evaluation [Heat resistance test] The laminated film was heated at 180°C for 60 minutes to harden the resin layer, forming an elastic resin layer. After removing the carrier film and protective film, a heat resistance test was performed on the elastic resin layer using a nitrogen reflow system (Tamura Manufacturing Co., Ltd., TNV-EN) in a temperature profile shown in Figure 3 in accordance with IPC / JEDEC J-STD-020. The elongation and tensile modulus of the elastic resin layer were measured before and after the heat resistance test. The conductor substrate was also subjected to the same heat resistance test, and the 90° peel strength was measured before and after the heat resistance test.
[0112] [Tensile modulus and elongation at break] A rectangular elastic resin layer test piece 40 mm long and 10 mm wide was prepared. A tensile test of this test piece was performed using an autograph (Shimadzu Corporation "EZ-S") to obtain a stress-strain curve. The tensile modulus and breaking elongation were obtained from the obtained stress-strain curve. The tensile test was performed under conditions of a chuck distance of 20 mm and a tensile speed of 50 mm / min. The tensile modulus was obtained from the slope of the stress-strain curve in the stress range of 0.5 to 1.0 N. The strain at the time when the test piece broke was recorded as the breaking elongation.
[0113] [Adhesion (90 degree peel strength)] The 90-degree peel strength between the copper foil and the elastic resin layer was measured by a peel test in which the copper foil was peeled off from the conductive substrate at a peel angle of 90 degrees.
[0114] [tack] The laminated film was heated at 180°C for 60 minutes to harden the resin layer, forming an elastic resin layer. The carrier film and protective film were removed from the hardened laminated film to prepare a laminated film test piece with a length of 70 mm and a width of 20 mm. The tack of the exposed surface of the elastic resin layer was measured using a tack tester ("TACII" manufactured by Rhesca Co., Ltd.). The measurement conditions were set to constant load mode, immersion speed of 120 mm / min, test speed of 600 mm / min, load of 100 gf, load retention time of 1 s, and temperature of 30°C.
[0115] [Table 2]
[0116] As shown in Table 2, the elastic resin layers of Examples 2-1 and 2-2 maintained excellent elasticity and high adhesion to the copper foil even after the heat resistance test. In addition, the tack of the elastic resin layer was appropriately low, and the handleability of the elastic resin layer was also excellent.
[0117] High temperature long-term storage test The laminated film was heated at 180°C for 60 minutes to harden the resin layer, forming an elastic resin layer. The carrier film and protective film were removed from the hardened laminated film, and the elastic resin layer was left in a safety oven (ESPEX Co., Ltd., SPH(H)-102) in the atmosphere at 160°C for 168 hours to carry out a high-temperature long-term storage test. The breaking elongation and elastic modulus before and after the high-temperature long-term storage test were measured under the same conditions as described above. In addition, the appearance of the elastic resin layer after the high-temperature long-term storage test was visually observed to confirm the presence or absence of discoloration. For Example 2-2, the adhesion was also evaluated.
[0118] [Table 3]
[0119] As shown in Table 3, the elastic resin layer of Example 2-2 containing an antioxidant showed little change in properties and no discoloration even after a high-temperature long-term storage test at 160°C for 168 hours. The elastic resin layer of Example 2-1 maintained its initial properties in the heat resistance test, but showed changes in properties after a more severe high-temperature long-term storage test. It can be said that the application of an antioxidant is effective especially in applications requiring high heat resistance.
[0120] Study 3 Example 3-1 [Preparation of Laminate with Conductor Layer] The protective film was peeled off from the laminated film A of Study 1, and the elastic resin layer was immersed in a mixture of Swelling Dip Securigant P (1000 mL / L, Atotech, product name) and NaOH: 3 g / L at 70 ° C. as a swelling liquid for 5 minutes. Next, the elastic resin layer was immersed in a mixture of Concentrate Compact CP (640 mL / L, Atotech, product name) and NaOH: 40 g / L at 70 ° C. as a roughening liquid for 10 minutes. Subsequently, the elastic resin layer was immersed in a mixture of Reduction Solution Securigant P500 (200 mL / L, Atotech, product name) and H2SO4: 100 mL / L at 40 ° C. as a neutralizing liquid for 5 minutes. Next, as a pretreatment for electroless plating, the elastic resin layer was immersed in cleaner Securigant 902 (40 mL / L, Atotech, product name) as a conditioner solution at 60 ° C for 5 minutes, and then washed with water. Next, as a pre-dip process, the elastic resin layer was immersed in a mixed solution of Predip Neoganth B (20 mL / L, Atotech, product name) and sulfuric acid (1 mL / L) at 25 ° C for 1 minute. Next, as a catalyst application process, the elastic resin layer was immersed in a mixed solution of Activator Neoganth 834 Conc. (40 mL / L, Atotech, product name), sodium hydroxide (4 g / L), and boric acid (5 g / L) at 35 ° C for 5 minutes. Next, as a reduction step, the elastic resin layer was immersed in a mixture of Reducer Neoganth WA (5 mL / L, Atotech, product name) and Reducer Accelerator 810mod (100 mL / L, Atotech, product name) at 25 ° C. for 1 minute. Then, as an electroless copper plating step, the elastic resin layer was immersed in a mixture of Basic Solution Printganth MSK (80 mL / L, Atotech, product name) and Copper Solution Printganth MSK (40 mL / L, Atotech, product name), Reducer Cu (14 mL / L, Atotech, product name), and Stabilizer Printganth MSK (3 mL / L, Atotech, product name) at 28 ° C. for 15 minutes to form a copper plating film with a thickness of about 0.5 μm on the elastic resin layer. After that, it was dried at 80 ° C. for 15 minutes using a dryer, and copper plating was further formed by copper sulfate electroplating. Thereafter, an annealing treatment was carried out at 150° C. for 30 minutes to obtain a laminate having a conductor layer with a thickness of 5 μm on the surface of the elastic resin layer.
[0121] Example 3-2 A laminated film having an uncured resin layer was obtained in the same manner as in Example 3-1, except that the resin varnish A was changed to the resin varnish B of Study 1. After peeling off the protective film from the laminated film, the laminated film was exposed to ultraviolet light (wavelength 365 nm) at 2000 mJ / cm using an ultraviolet exposure machine (Mikasa Co., Ltd. "ML-320FSAT"). 2 The resin layer of the laminated film was cured to form an elastic resin layer. A conductor layer was formed on the formed elastic resin layer by plating in the same manner as in Example 3-1, to obtain a laminated plate with a conductor layer.
[0122] Example 3-3 A laminated film having an uncured resin layer was obtained in the same manner as in Example 3-1, except that the resin varnish A was changed to the resin varnish C of Study 1. The resin layer was then cured using a dryer at 180°C for 1 hour to form an elastic resin layer. A conductor layer was formed by plating on the formed elastic resin layer in the same manner as in Example 3-1 to obtain a laminated plate with a conductor layer.
[0123] Comparative Example 3-1 A laminated film having an uncured resin layer was obtained in the same manner as in Example 3-1, except that the resin varnish A was changed to the resin varnish D of Study 1. The resin layer was then cured using a dryer at 180°C for 1 hour to form an elastic resin layer. A conductor layer was formed by plating on the formed elastic resin layer in the same manner as in Example 3-1 to obtain a laminated plate with a conductor layer.
[0124] [Fabrication and evaluation of wiring boards] As shown in FIG. 2, a test wiring board 1 was produced having an elastic resin layer 3 and a conductor plating film having a wave pattern formed on the elastic resin layer 3 as a conductor layer 5. First, an etching resist (Hitachi Chemical Co., Ltd., Photec RY-5325, product name) was attached to the conductor layer of each conductor layer-attached laminate using a roll laminator, and a phototool with a wave pattern formed thereon was attached to the etching resist. The etching resist was exposed to light at 50 mJ / cm using an EXM-1201 exposure machine manufactured by Oak Manufacturing Co., Ltd. 2 The etching resist was exposed to light with an energy of 1000 W. Then, spray development was performed for 240 seconds with a 1 wt % sodium carbonate aqueous solution at 30° C. to dissolve the unexposed parts of the etching resist and form a resist pattern with a wavy opening. Next, the copper foil in the part not covered by the resist pattern was removed with an etching solution. After that, the etching resist was removed with a stripping solution to obtain a wiring board 1 having a conductive plating film 5 on an elastic resin layer 3, the conductive plating film 5 forming a wavy wiring pattern with a wiring width of 50 μm and meandering along a predetermined direction X. The obtained wiring board was tensile deformed to a strain of 10% in the X direction and then returned to its original state, and the elastic resin layer and the corrugated wiring pattern were observed. The elastic resin layer and the wiring pattern were rated as "A" if they did not break when stretched, and "C" if they did break.
[0125] [Table 4]
[0126] The evaluation results of Examples 3-1 to 3-3 and Comparative Example 3-1 are shown in Table 4. It was found that in the wiring boards having a corrugated wiring pattern formed by the conductor substrates (laminates with conductor layers) of Examples 3-1 to 3-3, the elastic resin layer did not break even at 10% elongation, and the appearance of the corrugated wiring pattern was also satisfactory. On the other hand, in Comparative Example 3-1, since the resin layer had no elasticity, it broke before 10% elongation, and the wiring also broke at the same time. [Industrial Applicability]
[0127] The conductor substrate of the present invention and the wiring substrate obtained therefrom are expected to be used, for example, as substrates for wearable devices. [Explanation of symbols]
[0128] 1...wiring board, 3...elastic resin layer, 5...conductor layer (conductor foil or conductor plating film).
Claims
1. An elastic resin layer; A conductive substrate comprising: a conductive foil provided on the elastic resin layer.
2. 2. The conductive substrate according to claim 1, wherein the conductive foil has an elastic modulus of 40 to 300 GPa.
3. An elastic resin layer; A conductive plated film provided on the elastic resin layer.
4. The conductive substrate according to any one of claims 1 to 3, wherein the elastic resin layer has a recovery rate of 80% or more after being tensile-deformed to a strain of 20%.
5. The elastic resin layer contains a rubber component (A), The conductive substrate according to any one of claims 1 to 4, wherein the rubber component comprises at least one rubber selected from the group consisting of acrylic rubber, isoprene rubber, butyl rubber, styrene butadiene rubber, butadiene rubber, acrylonitrile butadiene rubber, silicone rubber, urethane rubber, chloroprene rubber, ethylene propylene rubber, fluororubber, vulcanized rubber, epichlorohydrin rubber, and chlorinated butyl rubber.
6. The conductive substrate according to any one of claims 1 to 5, wherein the elastic resin layer comprises a cured product of a resin composition containing a rubber component (A).
7. The conductive substrate according to claim 6 , wherein the rubber component (A) includes a rubber having a crosslinking group.
8. The conductive substrate according to claim 7 , wherein the crosslinking group is at least one of an acid anhydride group and a carboxyl group.
9. The conductive substrate according to any one of claims 6 to 8, wherein the resin composition further contains (B) a crosslinking component.
10. 10. The conductive substrate according to claim 9, wherein the crosslinking component (B) comprises a compound having at least one reactive group selected from the group consisting of a (meth)acrylic group, a vinyl group, an epoxy group, a styryl group, an amino group, an isocyanurate group, a ureido group, a cyanate group, an isocyanate group, and a mercapto group.
11. The conductive substrate according to any one of claims 6 to 10, wherein the resin composition further contains (C) at least one of a curing agent or a curing accelerator.
12. The conductive substrate according to any one of claims 5 to 11, wherein the content of the rubber component (A) is 30 to 100 mass% relative to 100 mass% of the elastic resin layer.
13. The conductive substrate according to any one of claims 1 to 12, wherein the elastic resin layer further contains an antioxidant.
14. A wiring board comprising the conductor substrate according to claim 1 or 2, wherein the conductor foil forms a wiring pattern.
15. A wiring board comprising the conductor substrate according to claim 3 , wherein the conductor plating film forms a wiring pattern.
16. A stretchable device comprising: the wiring board according to claim 14; and an electronic element mounted on the wiring board.
17. The conductor substrate according to claim 1 or 2, which is used to form a wiring substrate, the wiring substrate comprising a conductor substrate having an elastic resin layer and a conductor foil provided on the elastic resin layer, the conductor foil forming a wiring pattern.
18. The conductive substrate according to claim 3, which is used to form a wiring substrate, the conductive substrate comprising a conductive substrate having an elastic resin layer and a conductive plating film provided on the elastic resin layer, the conductive plating film forming a wiring pattern.
19. A step of preparing a laminate having an elastic resin layer and a conductor foil laminated on the elastic resin layer; forming an etching resist on the conductor foil; a step of exposing the etching resist and developing the exposed etching resist to form a resist pattern that covers a portion of the conductor foil; removing the conductor foil from a portion not covered by the resist pattern; The method for manufacturing a wiring board according to claim 14 , further comprising the step of: removing the resist pattern.
20. forming a plating resist on the elastic resin layer; a step of exposing the plating resist and developing the exposed plating resist to form a resist pattern that covers a portion of the elastic resin layer; forming a conductive plating film by electroless plating on a surface of the elastic resin layer in a portion not covered by the resist pattern; The method for manufacturing a wiring board according to claim 15 , further comprising the step of: removing the resist pattern.
21. forming a conductive plating film on the elastic resin layer by electroless plating; forming a plating resist on the conductor plating film; a step of exposing the plating resist and developing the exposed plating resist to form a resist pattern that covers a portion of the elastic resin layer; forming a further conductive plating film by electrolytic plating on the conductive plating film in the portion not covered by the resist pattern; removing the resist pattern; The method for producing a wiring board according to claim 15, further comprising a step of removing a portion of the conductive plating film formed by electroless plating that is not covered by the conductive plating film formed by electrolytic plating.
22. forming an etching resist on the conductor plating film formed on the elastic resin layer; a step of exposing the etching resist and developing the exposed etching resist to form a resist pattern that covers a part of the elastic resin layer; removing the conductor plating film from the portion not covered by the resist pattern; removing the resist pattern; The method for manufacturing the wiring substrate according to claim 15 , comprising:
Citation Information
Patent Citations
Manufacture of printed circuit board
JP1993041575A
Manufacture of copper polyimide board
JP1993090737A
Formation of conductor circuit by additive method
JP1993090739A
Flexible wiring board
JP2000151030A
Copper clad laminate for high-frequency substrate and surface-treated copper foil
JP2015013474A